Distribucion arborea de los gastropodos cerithidea montagnei (mollusca potamidae) y littorina Spp. (Mollusca, Littorinidae) en el manglar de Mata de Limón, Costa Rica (ING) - Suárez B, Edgar (1984)
The distribution and substrate preferences by the gastropods Cerithidea montagnei spp. were studied in mangroves located in Mata, Limón, Puntarenas, Costa Rica.  Four mangrove species were studied and the number, presence or absence of snails were recorded between September 1982 and June 1983. The order of susbtract preference for both snails was: 1) Rhizophora mangle, 2) Avicennia germinans, 3)Pelliciera rhizophorae and 4) Laguncularia racemosa. The possible reasons for the preference observed and discussed. The Gastropod certhidea montagnei showed a broader horizontal distribution as well greater densities than species of Littorina.